KETERKAITAN ANTARA EKSPANSI MONETER DENGAN AGREGATE DEMAND - Syaipan Djambak (Department of Development Economics, Universitas Sriwijaya, 2010)
Monetary expansion is the monetary policy pursued by the monetary authority by adding the amount of currency in circulation so that the total amount of money in circulation increases. Added Theoretically the money supply would encourage economic actors (consumers, producers and traders) to increase its activity which affects the increase in aggregate demand. This study will prove whether empirically (especially for the Indonesian economy) increase the money supply will boost aggregate demand. Authentication is done by using a sequential model equation (equation partial) which is a series of simple linear model using OLS and test methods hypotesia